IMPLEMENTASI LOGIKA PEMROGRAMAN DALAM PEMBUATAN GAME SEDERHANA MENGGUNAKAN SCRATCH BERBASIS MODUL PEMBELAJARAN BAGI SISWA/I PUSAT KEGIATAN BELAJAR MASYARAKAT SELUAS CITA NUSANTARA - Ayesha Faiqa Nayyara; Bagus Pangestu; Fadhilatu Aisyah Ariani; Arya Saputra Adianto; Ade Sepriansyah; Salsha Trianingsih; Nabila Eka Aurul'aeni; Revi Fahrizqi; Ichsan Arrizqi; Muhammad Brata Ilham Mariko; Aniq Astofa (Abdi Jurnal Publikasi, 2026)
The rapid development of digital technology has encouraged the use of interactive media as an effective learning tool, one of which is educational games. This study aims to implement programming logic in the game development process and analyze its role in improving logical thinking and problem-solving skills. The method used is a software engineering approach consisting of requirement analysis, design, implementation, and testing stages. The game is developed using fundamental programming logic concepts such as conditional statements, loops, and simple data structures integrated into the gameplay mechanics. The results show that the implementation of programming logic in game development not only produces an interactive and engaging product but also helps users understand logical concepts more intuitively. Therefore, the developed game has the potential to become an alternative learning medium to enhance computational thinking skills.